Exploring counterintuitive investing strategy : does the “dead cat” really bounce? - Chan, Li Ru. (2010)
In this paper, the success of Platt’s (2005) counterintuitive strategy was re-investigated. His methodology was replicated in the New York Stock Exchange and NASDAQ but covered an extended period from 1990 to 2009. In addition, several other factors such as the effects of bid/ask spread on returns, adjusting the returns for market performance, the implications of eliminating illiquid stocks when applying the strategy, and its feasibility after taking into account brokerage commissions were investigated. The results were examined based on the strategy’s feasibility in different market conditions, its optimal holding period, as well as the risk it carries. The study was also extended to the Tokyo Stock Exchange and Singapore Exchange. Results showed that the strategy provided substantial short term trading success in all markets investigated, even after adjusting for market performance, liquidity and risk. The strategy also worked regardless of bull or bear market conditions, but appeared to work better in bull periods, and the optimal holding period was consistently one day. This validated the results presented by Platt. However, when bid/ask spread and brokerage commissions were taken into account, the potential profits were entirely eroded.